Teachers Learning Classroom Sociology and Social Justice in Primary Education - Büşra Tombak İlhan; Bülent Alcı; Dilek Güven-Hastürk (University of Windsor, 2023)
Classroom sociology is a powerful discipline that helps students develop a sense of identity, achieve success, and experience well-being while building a strong community in the classroom. Teachers who can see beneath the surface and are aware of classroom sociology create a better and more just learning environment for learners, especially in primary education. This study focuses on improving teachers' classroom sociology and social justice awareness. Researchers designed a four-week in-service classroom sociology program for primary school teachers. The program aimed to improve the teachers' awareness and behaviours in terms of classroom sociology and social justice. This applied research was conducted using an in-service program intervention with 12 primary school teacher participants. Data was collected from in-class observations, teacher ethnography notes, participant evaluations, and classroom observations. Initially, participants were more focused on academic performance and teaching routines and largely ignored the social context of the classroom. At the end of the study, teacher participants' awareness of classroom sociology and social justice increased, and both their attitudes towards their students and their teaching methods changed in a positive manner.